Partisipasi Mahasiswa KKP Desa Nyurlembang Dalam Program Operasi Plastik Awet Muda Sebagai Upaya Menjaga Lingkungan - Nabila, Riska (JCSE: Journal of Community Service and Empowerment, 2023)
The use of plastic has expanded in various aspects of daily life, including household appliances, automotive, electronics, medical equipment, and agriculture. However, the extensive use of plastic also brings about negative consequences in the form of increased plastic waste, which is challenging to decompose and can harm the environment while posing health risks. The "Youthful Plastic Operation" program, implemented in Narmada District, West Lombok Regency, offers a practical solution to address the plastic waste issue. This program actively engages KKP UIN Mataram Nyurlembang Village students in cleaning activities and educating the local community. The active participation of KKP students has a positive impact on mitigating plastic waste and raising public awareness. It is hoped that this program can be expanded, accompanied by educational outreach, and subject to regular evaluations to achieve a more significant impact in preserving a clean and healthy environment.